The career trajectories of two world champion boxers: interpretive thematic analysis of media stories - Bonhomme, J.; Seanor, M.; Schinke, R. J.; Stambulova, N. B. (Sport in Society: Cultures, Commerce, Media, Politics, 2020)
Athlete development can be described through transitions that mark turning phases throughout athletes` careers. Our authors explored media data to unpack the career developments of two prominent world champion boxers from their early lives to world championship status. Employing thematic analysis, five themes were identified: (1) weathering hardships of early life (subthemes: the rough life of an innercity kid; abject poverty in war-torn Philippines), (2) entry into sport (subthemes: groomed to fight; boxing to escape poverty), (3) amateur experience (subthemes: Olympic medallist en route to the pros; struggling amateur with dreams of greatness), (4) launching a professional career (impressive American prospect; a charismatic unpolished slugger) and (5) capturing a world title (subthemes: the much-anticipated world champion; the unexpected world champion). This exploration augments our understanding of how two world-renowned boxers` career developments were represented through sport media and interpreted by the researchers, suggesting parallel pathways for future career boxers and those who work with them.